Small states and regional stability in South Asia - Kabir, Humayun; Bangladesh Institute of International and Strategic Studies (Dhaka : The University Press, 2005)
Contributed articles on political conditions in South Asia presented and discussed in many workshops and seminars.
Includes bibliographical references and index.
Keywords: States, Small -- Congresses; South Asia -- Politics and government -- Congresses